2019
DOI: 10.1038/s41598-019-55284-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Induce Podocyte Protection in the Puromycin Injury Model

Abstract: Podocytes are specialized cells with a limited capacity for cell division that do not regenerate in response to injury and loss. Insults that compromise the integrity of podocytes promote proteinuria and progressive renal disease. The aim of this study was to evaluate the potential renoprotective and regenerative effects of mesenchymal stromal cells (mSC) in a severe form of the podocyte injury model induced by intraperitoneal administration of puromycin, aggravated by unilateral nephrectomy. Bone derived mSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(50 reference statements)
6
10
0
Order By: Relevance
“…The positive effects of ASCs administration in reducing proteinuria levels are possibly due to direct effects on the glomerular filtration barrier, particularly on the structural and functional integrity of podocytes. We have recently reported renoprotective effects of MSC in a podocytopathy model induced by puromycin aminonucleoside recovering WT1 expression, ameliorating podocyte slit diaphragm and cytoskeletal proteins, such as nephrin and podocin synaptopodin and podocalyxin [25]. Similar results using BM-MSC in diabetic mice were reported by Wang and coworkers [26].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The positive effects of ASCs administration in reducing proteinuria levels are possibly due to direct effects on the glomerular filtration barrier, particularly on the structural and functional integrity of podocytes. We have recently reported renoprotective effects of MSC in a podocytopathy model induced by puromycin aminonucleoside recovering WT1 expression, ameliorating podocyte slit diaphragm and cytoskeletal proteins, such as nephrin and podocin synaptopodin and podocalyxin [25]. Similar results using BM-MSC in diabetic mice were reported by Wang and coworkers [26].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, tubular function was also improved in animals treated with ASCs, as measured by the fractional excretion of sodium and fractional excretion of potassium. We have previously described renoprotective effects of BM-MSCs treatment in the rat remnant kidney model and in the puromycin model [15,25]. These effects were also described in models of experimental glomerulonephritis [27] and renal transplantation [28] treated with BM-MSC and sepsisinduced kidney injury, treated with human wharton's jelly-derived MSC [29].…”
Section: Discussionmentioning
confidence: 91%
“…Recently, dysfunction of podocytes is identifi ed as the pathogenesis of DN, might participate in the early stages of this disease (14,15). The cytoskeletal pro tein (synaptopodin) and the slit diaphragm (podocin) are performed to the functional and structural integrity of podocytes (16). High glucose-induced low expression of podocin and synaptopodin was dramatically enhanced by EPA administration, which may indicate that EPA can affect the function of podocyte.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs promoted accelerated M2-polarized macrophage infiltration, trophic factors secretion, tubular epithelium proliferation, renal function improvement and IL-6 and TNFα reduction in mice with rhabdomyolysis-induced AKI [ 152 ]. Other studies also reported that MSCs promoted an increased expression of IL-10 and IL-4 mRNA, decreased expression of IL-1β and TNF-α mRNA, and decreased inflammatory cells infiltration, reduced a proinflammatory (Th1) environment, and increased anti-inflammatory effects (Th2) [ 147 , 153 , 154 ].…”
Section: Mscs-based Therapies For Multiple Organs Affected By Covid-1mentioning
confidence: 99%
“…MSC transplantation into the renal subcapsular region of rats with podocyte injury induced by puromycin promoted blood pressure reduction and decreased proteinuria, albuminuria, and serum creatinine. Renal regenerative and reparative effects of MSCs are also related to restoration of Wilms' tumor suppressor 1 (WT1) and VEGF expression and improvement of podocytes' functional and structural integrity, including proteins such as nephrin and podocin (slit diaphragm), synaptopodin, and podocalyxin (cytoskeletal proteins) [ 154 ]. Marrow mononuclear cell fraction, that includes MSC and other progenitor cells, can also promote renal tissue restoration [ 155 ].…”
Section: Mscs-based Therapies For Multiple Organs Affected By Covid-1mentioning
confidence: 99%